Enhanced photocatalytic degradation of malachite Green on spinel ferrite (nickel/ magnesium ferrite) Under direct sun light - A. ABILARASU; T. SOMANATHAN; A. SARAVANAN; V. SARAVANAN; P. RAJAKUMAR (International Journal of Pharma and Bio Sciences, 2016)
Ni/MgFe2O4 (NMF) nanocomposite were synthesized by solution combustion method and tested its activity under visible active photocatalyst for degradation of malachite green dye (MG). The structure and morphology of ferrite catalyst were characterized by powder X-ray diffraction (XRD) and scanning electron microscopy (SEM). The formation of cubic spinel structure was confirmed by powder x-ray diffraction (XRD). The morphology of the photocatalyst were shown by SEM, which have flakes like structure. The nanoparticles showed an excellent sunlight driven photocatalytic activity to malachite green in water. The efficiency of photodegradation and mineralization studies was optimized by varying parameters such as concentration of H2O2, pH and catalyst weight. The mineralization of MG has been confirmed by COD measurements. The results give a clear idea that NMF can be utilized as promising photocatalyst under visible light for organic pollutant degradation.